Accounting information systems - Romney, Marshall B; Steinbart, Paul John (Hoboken : Pearson Education, 2021)
"This book is intended for use in a one-semester course in accounting information systems at either the undergraduate or graduate level. The topics covered in this text provide information systems students with a solid understanding of transaction processing systems that they can then build on as they pursue more in-depth study of specific topics such as databases, data analytics, networks, systems analysis and design, cloud computing, virtualization, blockchain, artificial intelligence, Internet of Things, computer security, and information system controls"--
Revised edition of the authors' Accounting information systems, [2018]
Includes index.
Keywords: Accounting -- Data processing; Information storage and retrieval systems -- Accounting